Population genetics of the critically endangered three-striped turtle, Batagur dhongoka, from the Ganga river system using mitochondrial DNA and microsatellite analysis - Ajit Kumar; Ashish Kumar Panda; Aftab Alam Usmani; Prabhaker Yadav; Anshu Panwar; Ruchi Badola; Syed Ainul Hussain; Sandeep Kumar Gupta (Scientific Reports, 2024)
Abstract The three-striped roofed (Batagur dhongoka) is a semi-aquatic turtle that belongs to family Geoemydidae. Due to anthropogenic pressure, it has been facing an intense decline of over 80% in its distribution range in the past 50 years. It is considered as 'Critically Endangered' so effective conservation strategies are needed to protect the species by determining their genetic diversity and population genetic structure. This study investigates the genetic diversity, population structure and demographic pattern of B. dhongoka from two Turtle Rescue and Rehabilitation Centre established near Ganga river using mitochondrial cytochrome b (Cyt b: 1140 bp) ; control region (CR: 451 bp) and ten nuclear microsatellite loci. mtDNA results show low levels of nucleotide diversity (π = 0.0022) in B. dhongoka haplotypes and provide evidence for a low substitution rate. The demographic pattern estimated by the Bayesian skyline plot (BSP) analysis indicates historical stability followed by growth in the effective population size, with a recent reduction in population size from ~ 2 thousand years ago. The microsatellite findings show a moderate level of observed heterozygosity (Ho: 0.49). Bayesian-based clustering analysis revealed weak genetic structures in B. dhongoka and presence of admixed assignations suggesting close genetic relationships. These findings shed light on B. dhongoka's genetic status and underline the necessity of comprehensive rehabilitation and relocation programs and conservation and management techniques to ensure the species' long-term survival. In order to ensure the effective protection and conservation of B. dhongoka, the Government of India has taken a proactive measure by incorporating it into Schedule I of the Wildlife (Protection) Act, 1972, as amended in 2022.